An Analysis of Electricity Generation with Renewable Resources in Germany - Mendoza Merchán, Eduardo Vicente; Velásquez Gutiérrez, Moisés David; Medina Montenegro, Diego Armando; Nuñez Alvarez, José Ricardo; Grimaldo Guerrero, John William (International Journal of Energy Economics and Policy, 2020)
Germany has an experience of renewable energy policies that encourages their usage, achieving technological migration and the redesign of its power generation matrix, achieving 112 GW of renewable resources at 2017. The research presents an analysis between the energy policies and the electricity statistics, the results forecast a date in which they will reach the goal of 50% of annual generation of total electric power by renewable sources, a goal set in 2012. Keywords: Energy policy, Renewable Energy, Forecasting, Energiewende. JEL Classifications: K29, Q48 DOI: https://doi.org/10.32479/ijeep.9369